Tampilan Bobot Badan dan Ukuran Linier Tubuh Domba Ekor Gemuk pada Umur Tertentu di Kabupaten Lombok Timur - Muhammad Ashari; Raden Roro Agustien Suhardiani; Rina Andriati (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2015)
A study on the performance of sheep production has been carried out in the enclave production of fat-tailed sheep (DEG) in East Lombok. The purpose of this study was to determine the production potential of fat-tailed sheep, which have been reared traditionally. The method that employed throughout the study was a survey related method. The locations of the study were decided according to the purposive sampling techniques based on the population density of DEG. Samples were collected randomly; as many as 20 individuals, 10 males and 10 females, each as a representative of any age group, which had previously been determined. The variables observed were the birth weight, weaning weight and adult weight as well as statistical measurements of the vital body, i.e. the body length and the chest circumference. Data on the performance of the production were analyzed and tested statistically using t-test. These studies suggest that gender affect significantly (P <0.05) for the body weight and the vital body measurements. The rams had higher body weight than the ewes. Furthermore, the linear body size of fat tailed-rams was larger than those of the fat-tailed ewes.